2013
DOI: 10.1080/17441692.2012.748085
|View full text |Cite
|
Sign up to set email alerts
|

Improving maternal health through social accountability: A case study from Orissa, India

Abstract: 2As maternal health specialists accelerate efforts toward MDG5a, attention is focusing on how to best improve service accountability to target communities as a strategy for more effective policy implementation. We present a case study of efforts to improve accountability in Orissa, India, focusing on the role of local women, intermediary groups, health providers, and elected politicians. We highlight three drivers of success: 1) the generation of demand for rights and better services, 2) the leverage of interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 21 publications
5
87
0
Order By: Relevance
“…Several authors underlined the importance of some contextual factors necessary to enable the harmonious implementation and smooth running of social accountability, which are lacking in these health zones, such as the existence of a coalition and social mobilization [26, 28, 33, 35, 4044]. Other authors stressed the importance of the capacity of community groups to express their views or to exert pressure on health providers or on the public authorities [45, 46], a well-functioning health committee [45, 47] especially considering the limited influence of health providers [48, 49], competent decentralization [45, 50], and the role of the media in providing access to information [28] as enabling factors of social accountability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors underlined the importance of some contextual factors necessary to enable the harmonious implementation and smooth running of social accountability, which are lacking in these health zones, such as the existence of a coalition and social mobilization [26, 28, 33, 35, 4044]. Other authors stressed the importance of the capacity of community groups to express their views or to exert pressure on health providers or on the public authorities [45, 46], a well-functioning health committee [45, 47] especially considering the limited influence of health providers [48, 49], competent decentralization [45, 50], and the role of the media in providing access to information [28] as enabling factors of social accountability.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding constraints, several authors have also identified some contextual factors that can hinder social accountability such as the low status of women [26, 44, 51, 52] and the identification of social actions promoting citizens’ interests as a political activity.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of this policy effort are the national and sub-national "citizen hearings" bringing stakeholders and policymakers together in policy dialogue (see also: http:// whiteribbonalliance.org/campaigns/ citizenshearings-2015/). 12 Tracking impact-In regard to evaluating the effect of advocacy, the lack of standard indicators, processes, and structures for monitoring and reviewing the Global Strategy and Every Woman Every Child has hindered efforts to improve quality and impact. It has also made it more challenging to build an investment case for advocacy.…”
Section: Problemsmentioning
confidence: 99%
“…The interface between politicians, technocrats, health service providers and grassrootslevel citizens in public decision-making arenas and through the media (box 3b) is expected to affect prioritisation and integration of maternal health needs in policies and budgets and increased internal monitoring of health service provision (box 3a), leading to improved and gender-responsive maternal health service delivery (box 4) respectively (Papp et al, 2013). The interface between health providers and citizens during citizen monitoring of health services at health facilities is expected to provide health workers with a better understanding of citizen needs, leading to improved and gender-responsive maternal health service delivery, illustrated by the arrow between boxes 3b and 4.…”
Section: Explicating the Programme Theorymentioning
confidence: 99%